Motivação para o cumprimento de normas de conduta social - Mendonça, Emilia Maria V. F. R. de (1987)
According to the theme, motivation changes behaviour and internalization is a factor of rule perception: 'Motivation acts as a main factor in the perception and execution of social conduct rules'. It is a survey based on personal characteristics found in high school students and their perception of public ethics-rules. Variables of personality and attitudes were analized by means of four different scales. A question public ethics was made tested. The way dealt with the scales and questionnaire statistically was evaluated by meas of multiple regression. The results have shown that the two variables measured (personality and attitude) proved to be quite correlated and reliable.